Cultural consensus in medicinal plant use among the Tangkhul Naga of Northeast India - Shimrah, Tuisem; Leisan, Judith; Lungleng, Peimi (Ethnobotany Research and Applications, 2026)
Background: Traditional medicinal knowledge is vital for meeting primary healthcare needs in rural and indigenous populations and in supporting biodiversity conservation. The Tangkhul Naga community of Manipur, located in the Indo-Burma Biodiversity Hotspot, maintains rich ethnobotanical traditions, but quantitative analyses of their medicinal plant knowledge remain limited. This study aims to document medicinal plant usage in Tangkhul and to assess which species are culturally and therapeutically most important. Methods: Data on medicinal plants were obtained through semi-structured interviews with the local informants. Quantitative botanical indices, including Informant Consensus Factor (ICF), Use Value (UV), and Fidelity Level (FL%), were applied to evaluate cultural consensus on ailments, species importance, and ailment-specific reliability of species. Results: ICF values across nine ailment categories ranged from 0.9350 to 1.0, indicating strong agreement among informants and a robust ethnomedicinal knowledge base. Species with high UVs included Allium hookeri (UV = 0.787), Aloe vera (UV = 0.697), and Ageratina adenophora (UV = 0.642) as culturally salient multipurpose plants. Species exhibiting perfect FL% (100), namely Acmella uliginosa, Ageratum conyzoides, and Allium sativum, showed very high reliability for specific ailments. The most reported ailment categories were skin and dermatological disorders, respiratory illnesses, and digestive-metabolic ailments. Conclusions: The findings show that Tangkhul traditional medicinal knowledge is both resilient and adaptive. Priority plant species identified here warrant pharmacological validation. Furthermore, these results highlight the need for initiatives in cultural preservation and sustainable species management to support both human health and biodiversity. Keywords: Tangkhul Naga; Ethnobotany; Medicinal plants; Traditional knowledge; Cultural consensus; Indo-Burma Biodiversity Hotspot